Estruturas de piada no trabalho plástico: conversas com Philip Guston - Carvalho, Bruno Moutinho de [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Nesta dissertação me propus falar sobre alguns dos trabalhos que construí entre 2018 e 2023, descortinando aspectos do processo e da estrutura desses trabalhos e suas relações com a linguagem da piada e do chiste. Apresento aproximações entre ditas estruturas e o trabalho do artista norte americano Philip Guston, numa conversa com alguns dos meus trabalhos.

In this dissertation, I have endeavored to delve into some of the works I’ve built between 2018 and 2023, unveiling aspects of their processes and structures, and exploring their connections with the language of humor and wit. I draw parallels between these structures and the artistic endeavors of the American artist Philip Guston, engaging in a dialogue with some of my own works.
Joke structures on visual work: conversations with Philip Guston
Keywords: Pintura; Escultura; Arte moderna - Séc. XXI; Arte - Humor; Painting; Sculpture